PERSEPSI ANALIS KARTU KREDIT TENTANG RESIKO KARTU KREDIT PADA BANK KONVENSIONAL DAN BANK SYARIAH - Hilda Febianne Prayogo (Jurnal Akuntansi Indonesia, 2014)
This study aimed to compare the perception of risk analysts credit card at conventional banks and Islamic banks , case studies on the BNI and BNI Syariah in Semarang which includes the process of risk management application, credit card risk identification and appearing stagnant credit card. This study was measured using a questionnaire method is to assess the perception of risk analysts credit card at conventional banks and Islamic banks . Then to compare the perception of risk analysts credit card at conventional banks and Islamic banks performed different tests using the Mann - Whitney test because the data presented is not normal , by ten respondents . The results of the research analyst ‘s perception of the risk of credit card shows that on each item tested on conventional banks aresuperior to Islamic banks when viewed from the mean rank in Mann Whitney rank output , but this difference was not significant , so that could be said about the credit card analyst perception risk credit card at conventional banks and Islamic banks are the same .